2008
DOI: 10.1073/pnas.0708451105
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish early cardiac connexin, Cx36.7/Ecx, regulates myofibril orientation and heart morphogenesis by establishing Nkx2.5 expression

Abstract: Heart development is a precisely coordinated process of cellular proliferation, migration, differentiation, and integrated morphogenetic interactions, and therefore it is highly susceptible to developmental anomalies such as the congenital heart disease (CHD). One of the major causes of CHD has been shown to be the mutations in key cardiac transcription factors, including nkx2.5. Here, we report the analysis of zebrafish mutant ftk that showed a progressive heart malformation in the later stages of heart morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…Besides its structural role at the Z-disc, CBF also regulates cardiac and skeletal sarcomerogenesis, because sarcomeres are significantly thinner in CBF morphants. Similar changes in myofilament structure can be observed in other models of heart failure and range from almost completely disrupted sarcomeric units, for example in the Troponin-T-deficient zebrafish mutant silent heart (tnnt2a), the Titin-deficient mutant pickwick and the cMLC2-deficient zebrafish mutant tell tale heart, to minor changes in the content, size or organization of sarcomeres in Tropomyosin-4-or connexin Cx36.7-deficient zebrafish Sehnert et al, 2002;Sultana et al, 2008;Xu et al, 2002;Zhao et al, 2008).…”
Section: (C-f)ultrastructural Analyses Of Ventricular Cardiomyocytessupporting
confidence: 53%
“…Besides its structural role at the Z-disc, CBF also regulates cardiac and skeletal sarcomerogenesis, because sarcomeres are significantly thinner in CBF morphants. Similar changes in myofilament structure can be observed in other models of heart failure and range from almost completely disrupted sarcomeric units, for example in the Troponin-T-deficient zebrafish mutant silent heart (tnnt2a), the Titin-deficient mutant pickwick and the cMLC2-deficient zebrafish mutant tell tale heart, to minor changes in the content, size or organization of sarcomeres in Tropomyosin-4-or connexin Cx36.7-deficient zebrafish Sehnert et al, 2002;Sultana et al, 2008;Xu et al, 2002;Zhao et al, 2008).…”
Section: (C-f)ultrastructural Analyses Of Ventricular Cardiomyocytessupporting
confidence: 53%
“…The mechanism behind these observed deformations requires further study; however, we have identified some key genes involved in cardiovascular development that are downregulated in cortisol-injected embryos. The cardiac transcription factor nkx2.5, which is involved in heart field definition and myofibril development (Chen and Fishman, 1996;Sultana et al, 2008), is suppressed at both 36 and 48 hpf. Knockdown of nkx2.5 has been shown to cause a variety of cardiac defects in heart chamber formation as well as pericardial edema (Targoff et al, 2008), similar to the phenotype observed in our cortisol-injected embryos.…”
Section: Discussionmentioning
confidence: 99%
“…A D12V mutation was identified in zebrafish CX36.7 (55); fish carrying this mutation show disorganization of myofibrils and cardiac malformations. This residue (which aligns with Asp-12 in human CX37) may be important for gap junction plaque formation and function, because the CX36.7D12V mutant shows impaired trafficking to the plasma membrane in HeLa cells (55) and a different substitution in mouse CX43 (D12S) causes loss of Lucifer yellow transfer, although CX43D12SGFP does form gap junction plaques in baby hamster kidney cells (23). Many of the mutants within the NT associated with oculodentodigital dysplasia (CX43) or with cataracts (CX50) occur in amino acid residues beyond the predominant helical structure (after amino acid 16).…”
Section: Discussionmentioning
confidence: 99%